2009
DOI: 10.1007/s11664-009-0916-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Property Evaluation of Sn-3.0A-0.5Cu BGA Solder Joints Using High-Speed Ball Shear Test

Abstract: The traditional ball shear test is not suitable for evaluating joint reliability under drop loading, since the applied test speeds, usually lower than 5 mm/s, are well below the impact velocity applied to the solder joint in a drop test. The present study expands recently reported research by investigating the effect of thermal aging on the joint strength and fracture mode of Sn-3.0Ag-0.5Cu ball grid arrays during high-speed shear testing, with a shear height of 50 lm and a shear speed ranging from 0.01 m/s to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A contradiction in such behavior is shown by Tee et al's (2003Tee et al's ( , 2006 finite element (FE) study, where the tin-lead solder stresses are decreased by 11% when the solder height is increased by 20%. In addition to solder dimensions, the copper pad finish and electroplating process have a significant effect on the mechanical response, that is, shear strength, of both lead-based and lead-free solder because of the formation of brittle intermetallic compound layers (IMCs) which further quicken the mechanical failure of the interconnects, especially when combined with aging processes (Lee et al, 2017;Ha et al, 2009;Yoo et al, 2009). Darveaux et al's (2015) experiments showed that the LGA reliability is approximately 1.5 times better than BGA in thermal cycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A contradiction in such behavior is shown by Tee et al's (2003Tee et al's ( , 2006 finite element (FE) study, where the tin-lead solder stresses are decreased by 11% when the solder height is increased by 20%. In addition to solder dimensions, the copper pad finish and electroplating process have a significant effect on the mechanical response, that is, shear strength, of both lead-based and lead-free solder because of the formation of brittle intermetallic compound layers (IMCs) which further quicken the mechanical failure of the interconnects, especially when combined with aging processes (Lee et al, 2017;Ha et al, 2009;Yoo et al, 2009). Darveaux et al's (2015) experiments showed that the LGA reliability is approximately 1.5 times better than BGA in thermal cycling.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical behavior assessment of electronic assemblies and handheld devices, like cell phones and tablets, under shock and impact has become a major goal in the past few decades. Therefore, researchers all over the globe have conducted numerous experiments, numerical and analytical research studies to properly evaluate the reliability and fatigue life behavior of electronic packages when exposed to impact loadings (Xi et al , 2015; Gharaibeh et al , 2013; Kallolimath and Zhou, 2016; Ghaffarian, 2022; Gharaibeh and Pitarresi, 2022). Besides, because of the continuous demand for thinner and more reliable devices, land grid array (LGA) interconnects are becoming an appealing and much fashionable design choice over the conventional ball grid array (BGA) solder balls (Joshi et al , 2012; Kujala et al , 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Although a great deal of research based on this experimental method has been conducted in the field of BGA solders, these research works mainly focus on solder ball materials and manufacturing processes. Their major task has been to distinguish the shear stress characteristics of tested solder balls under various different conditions, including alloy element proportions [ 2 , 12 , 13 , 14 , 15 ], manufacturing processes [ 16 , 17 ], solder ball dimensions [ 18 , 19 ], aging time [ 18 , 20 ], surface finish materials [ 1 , 21 , 22 ], and more. These research efforts have provided effective support in the procedures of material proportioning and manufacturing process design for highly reliable and stable lead-free solders.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the coefficient of thermal expansion (CTE) mismatch among the chips, solder joints and substrates, BGA solder joints are mainly subjected to shear stresses in service [2]. Consequently, solder ball shear tests have been widely adopted to evaluate the solder ball attachment strength in BGA joint packages [3][4][5][6][7][8]. Although ball shear tests can be used to evaluate the attachment strength quickly and conveniently, it cannot reflect the size and geometry effects of BGA solder joints accurately, where there are two attachment interfaces.…”
Section: Introductionmentioning
confidence: 99%